1993
DOI: 10.1037/0735-7036.107.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Personalities of octopuses (Octopus rubescens).

Abstract: Large individual differences are commonly found in the behavior of octopuses, even in standardized situations. Octopus rubescens (n = 44) were tested in 3 situations (alerting, threat, and feeding) to quantify this variation. A factor analysis of resulting behaviors isolated 3 orthogonal dimensions of their variability, Activity, Reactivity, and Avoidance, which accounted for 45% of the variance. The similarity of these factors to dimensions of personality in humans and individual differences in animals sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
105
1
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 32 publications
9
105
1
3
Order By: Relevance
“…guppies; Budaev, 1997), and even invertebrates (e.g. octopuses; Mather & Anderson, 1993). Finally, the characteristic of 'dominant' is encompassed by the trait of Extraversion in the human taxonomy (Goldberg, 1990), and is a particularly robust measure in chimpanzees, demonstrating the single highest factor weighting of any characteristic in the chimpanzee personality model (King & Figueredo, 1997), and both reliability (Freeman & Gosling, 2010), and external validity in predicting individual behaviour (Pederson, King & A shared signal system 5 Landau, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…guppies; Budaev, 1997), and even invertebrates (e.g. octopuses; Mather & Anderson, 1993). Finally, the characteristic of 'dominant' is encompassed by the trait of Extraversion in the human taxonomy (Goldberg, 1990), and is a particularly robust measure in chimpanzees, demonstrating the single highest factor weighting of any characteristic in the chimpanzee personality model (King & Figueredo, 1997), and both reliability (Freeman & Gosling, 2010), and external validity in predicting individual behaviour (Pederson, King & A shared signal system 5 Landau, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, cephalopods are the only invertebrate group that has been assessed for such variation. There were striking differences in the reactions of octopuses to a standard situation, leading Mather & Anderson (1993) to sort them into 3 personality dimensions, those of activity, reactivity and avoidance. Further work by Sinn et al (2001) revealed developmental trends in these dimensions.…”
Section: Assessment Of Learningmentioning
confidence: 99%
“…Although personality traits had been assessed in a variety of species, such as rhesus monkeys (Stevenson-Hinde & Zunz, 1978), hyenas (Gosling, 1998), and octopuses (Mather & Anderson, 1993), no research had explicitly compared assessments of humans and animals in a single design. Therefore, Gosling, Kwan, and John (2003a) examined side-by-side the accuracy of personality ratings of 78 dogs and their owners.…”
Section: Phase 2: Establish the Measurement Foundations And Develop Mmentioning
confidence: 99%